The Associations Between Prior Abuse Experiences and Causal Attributions for Intimate Partner Violence Among Service-Attending Husbands in Jordan - Maberah, Shooroq; Al-Rub, Mohammed Abu (Islamic Guidance and Counseling Journal, 2026)
Intimate partner violence (IPV) is a significant public health issue in Jordan, yet research on perpetrator cognition remains limited. While prior abuse is a known risk factor, its association with how perpetrators explain their own violence specifically through causal attributions is underexplored in this context. This study aimed to examine the associations between prior abuse experiences and causal attributions among service-attending husbands in Jordan who have perpetrated IPV. A descriptive correlational design was employed with a convenience sample of 120 husbands recruited from rehabilitation and judicial services. Participants completed the Abuse Experiences Inventory (AEI) and the Causal Attribution Inventory (CAI), with data analyzed using Pearson correlations. Results indicated moderate levels across all attribution dimensions (internal, external, stable, unstable). Domestic abuse was the most reported prior experience. Weak but statistically significant positive correlations were found between all abuse domains and attribution dimensions (r = .186–.206, p < .05), with the strongest link between domestic abuse and external attributions. These findings suggest a modest association between abuse history and attribution styles, highlighting the potential value of addressing cognitive factors in perpetrator interventions without diminishing personal accountability. The study contributes to a nuanced understanding of IPV perpetrators in Jordan and underscores the need for longitudinal research to clarify these relationships.